2007
DOI: 10.1029/2006jd007608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of several PM2.5 forecast models using data collected during the ICARTT/NEAQS 2004 field study

Abstract: [1] Real-time forecasts of PM 2.5 aerosol mass from seven air quality forecast models (AQFMs) are statistically evaluated against observations collected in the northeastern United States and southeastern Canada from two surface networks and aircraft data during the summer of 2004 International Consortium for Atmospheric Research on Transport and Transformation (ICARTT)/New England Air Quality Study (NEAQS) field campaign. The AIRNOW surface network is used to evaluate PM 2.5 aerosol mass, the U.S. EPA STN netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
159
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(166 citation statements)
references
References 47 publications
7
159
0
Order By: Relevance
“…Many chemistry-transport models underestimate the mass loadings of OA in the polluted atmosphere (16,31). However, the discrepancy is rarely an order of magnitude as suggested in the previous paragraph.…”
Section: Urban Sourcesmentioning
confidence: 95%
“…Many chemistry-transport models underestimate the mass loadings of OA in the polluted atmosphere (16,31). However, the discrepancy is rarely an order of magnitude as suggested in the previous paragraph.…”
Section: Urban Sourcesmentioning
confidence: 95%
“…One possibility is a collective misrepresentation of nighttime planetary boundary layer (PBL) dynamics and depositional loss. For NEAQS-2004, McKeen et al [2007 showed that the diurnal trends for urban and suburban locations were not reproduced adequately, and that the 24-h model averages were heavily skewed toward nighttime concentrations for most models, while the observations were not. This does not appear to be a factor for TexAQS II, since statistics based only on midday 8-h averages (not shown) are nearly identical to those shown in Figure 5 for TexAQS II, but were significantly different (much improved skill with an 11% median ensemble low bias) for NEAQS-2004.…”
Section: Threshold or Categorical O 3 Statistics For The Models And Ementioning
confidence: 99%
“…Comparisons with aircraft data given below (sections 4 and 5) suggest that highly reactive anthropogenic VOC emissions (ethylene in particular) are significantly underpredicted relative to NO x emissions in the Houston region, whereas inferred ethylene/NO x emission ratios for the Dallas/Forth Worth region (based on only one available upwind/downwind transect pair) are more consistent between all of the AQFMs and observations. Figure 1c, and compared with equivalent statistics for the ICARTT/NEAQS study period in the northeast United States and southeastern Canada during the summer of 2004 [McKeen et al, 2007]. Current regulatory interest is focused on 24-h average concentrations, which are used in the AIRNow comparisons here (0400 UTC to 2800 UTC model forecasts) for the 13 August to 30 September 2006 period.…”
Section: Threshold or Categorical O 3 Statistics For The Models And Ementioning
confidence: 99%
See 2 more Smart Citations